Evidence for an indigenous female mouse urobiome - Sidra Sohail; Daniel Bushnell; Mark Khemmani; Sridhar Narla; Olivia Lamana; Bhanu Sharma; Robert B. Moreland; Alan J. Wolfe; Catherine S. Forster (PLoS ONE, 2025)
Mice have been used as a valuable model for understanding pathophysiological mechanisms of urinary tract infection for almost six decades. Mice offer many advantages including genetic manipulation to test the role of genes and mechanisms, the availability of germ-free mice, and similarities to humans in innate immune defenses and the strain-dependent presence of vesicoureteral reflux. However, like with humans, the mouse bladder urine above the urinary sphincter has generally been assumed to be sterile. Yet, given the presence of urobiomes in other mammals and the emerging role of the human urobiome in the defense of the urinary bladder and upper urinary tract, the existence of a mouse urobiome should be critically examined as indigenous microbiota may influence experimental results. To determine if an indigenous murine urobiome exists, we obtained voided urine from two sets of female C57BL/6J mice during three different intervals using two different extraction and sequencing methods and analyzed them simultaneously by a single method. For one set, we also obtained urine by suprapubic aspiration, which we compared to the paired voided urine samples. We conclude that an indigenous murine urobiome exists and that voided urine contains post-urethral microbes.